Pembuatan Video Promosi Rumah Makan Angkringan Hamka Menggunakan Teknik Editing - Nuridayati Nuridayati; Subhan Hartanto; Agusdi Syafrizal (JURNAL VOKASI TEKNIK, 2026)
Angkringan Hamka Restaurant, known for its cozy atmosphere and unique place as well as typical dishes, has not yet utilized a promotional video to showcase its unique qualities to a broader audience. To address this, a promotional video was created using editing techniques that incorporate sound effects and voice-over elements. These elements were designed to produce an informative and engaging video capable of conveying the ambiance and distinctiveness of Angkringan Hamka to the public. The video production process involved four main stages: pre-production, which included idea development, scriptwriting, and storyboard creation; production, covering footage capture and the recording of narration and sound effects; post-production, consisting of video editing, combining visual and audio elements, and adding color grading; and finally, distribution through YouTube and other social media platforms. The resulting video successfully highlighted the ambiance, facilities, and signature menu of Angkringan Hamka, receiving positive feedback from viewers who appreciated its visual appeal and clear messaging. The innovative aspect introduced was the use of sound effects and voice-over in editing techniques to create an audiovisual experience that feels immersive and lifelike, thereby enhancing the promotional appeal and establishing a new model for marketing local culinary businesses.